Corporate Citizenship: How to Strengthen the Social Responsibility of Managers? - Grit, Kor (Journal of business ethics, 2004)
Corporate citizenship challenges the foundations and working of the basic institutions market, state and civil society. These institutional changes complicate the work of the manager, because the responsibilities of management are not only increasing, they are also becoming vaguer and more elusive. In this paper, I will analyze the new, complex responsibilities of management in terms of the scope and the legitimizationof corporate citizenship. What may we expect of individual organizations? Which wishes of which stakeholders should be honored? How can we legitimize the new societal and public role of business firms? The outcome of this analysis will be translated to the practice of management; how can we strengthen the social responsibility of managers? Four options will be discussed. (1) Market regulation, which binds the actions of managers. (2) Professionalization of management, which seeks for better information. (3) Moral management, which incorporates norms and values from outside the market. (4) Stakeholder management, which leaves room for the participation of stakeholders. These options can be schematized according to an internal-external axis and an objective-subjective axis. I will show that stakeholder management fits the best with the idea of corporate citizenship, but has serious risks of failing.